2016
DOI: 10.1007/s00208-016-1482-2
|View full text |Cite
|
Sign up to set email alerts
|

Sums of Euler products and statistics of elliptic curves

Abstract: Abstract. We present several results related to statistics for elliptic curves over a finite field F p as corollaries of a general theorem about averages of Euler products that we demonstrate. In this general framework, we can reprove known results such as the average LangTrotter conjecture, the average Koblitz conjecture, and the vertical Sato-Tate conjecture, even for very short intervals, not accessible by previous methods. We also compute statistics for new questions, such as the problem of amicable pairs … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 40 publications
0
20
0
Order By: Relevance
“…satisfies the general framework of Theorem 4.2 of [6] and thus, by [6, Formula (6.10)], we have ∆ ℓ ≪ 1/ℓ 3/2 for sufficiently large ℓ. Therefore c t 1 ,t 2 is given by the convergent Euler product in Theorem 1.4.…”
Section: The Law Of Large Numbersmentioning
confidence: 80%
See 1 more Smart Citation
“…satisfies the general framework of Theorem 4.2 of [6] and thus, by [6, Formula (6.10)], we have ∆ ℓ ≪ 1/ℓ 3/2 for sufficiently large ℓ. Therefore c t 1 ,t 2 is given by the convergent Euler product in Theorem 1.4.…”
Section: The Law Of Large Numbersmentioning
confidence: 80%
“…, 6 where the superscript (p) means that the matrices A ∈ GL 2 (Z/ℓ k Z) satisfy the extra condition det(A) = p. Note that, for ℓ p, f ℓ (t, p) is similar to the ℓ-factor of the universal constant c t in (1) with the imposed extra condition det(A) = p. Gekeler has shown that in (8) the limit exists. More precisely,…”
Section: Introductionmentioning
confidence: 99%
“…We note that the result of Banks and Shparlinski (and that in Theorem 1.1) gives a true error term only when the size of the interval I is greater that p −1/4+ε . This was improved (on average) by Baier and Zhao in [1] and recently by David et al [4], where the effective version of Birch's theorem is shown to hold for intervals I of length greater than p −1/2+ε , although in these cases the saving is only a power of a logarithm over the main term.…”
Section: Introductionmentioning
confidence: 94%
“…Framework. As in [6], we begin with an arbitrary framework. For every prime Q suppose we have a function δ(u; Q) such that Here the product is an infinite product over all the monic prime polymials in F q [X].…”
Section: Summing the Primesmentioning
confidence: 99%
“…Recently David, Koukoulopoulos and Smith [6] studied sums of Euler products over rational primes and their applications to statistics of elliptic curves. We will use similar techniques as them and apply it to summing Euler products in the function field setting.…”
Section: Summing the Primesmentioning
confidence: 99%